Reconstruction with 3D-printed prostheses after type I + II + III internal hemipelvectomy: Finite element analysis and preliminary outcomes - Guo, Zehao; Peng, Yongjun; Shen, Qiling; Li, Jian; He, Peng; Yuan, Peng; Liu, Yulei; Que, Yukang; Guo, Wei; Hu, Yong; Xu, Shenglin (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Prosthetic reconstruction after type I + II+ III internal hemipelvectomy remains challenging due to the lack of osseointegration and presence of giant shear force at the sacroiliac joint. The purpose of this study was to evaluate the biomechanical properties of the novel 3D-printed, custom-made prosthesis with pedicle screw–rod system and sacral tray using finite element analysis. Methods: Four models that included one intact pelvis were established for validation. Forces of 500 N and 2,000 N were applied, respectively, to simulate static bipedal standing and the most loaded condition during a gait cycle. Biomechanical analysis was performed, and the results were compared; the preliminary outcomes of four patients were recorded. Results: For the reconstructed hemipelvis, stress was mainly concentrated on the sacral screws, bone–prosthesis interface, and upper endplate of the L5 vertebra. The optimization of the design with the sacral tray structure could decrease the peak stress of the sacral screws by 18.6%, while the maximal stress of the prosthesis increased by 60.7%. The addition of the lumbosacral pedicle–rod system further alleviated stress of the sacral screws and prosthesis by 30.2% and 19.4%, respectively. The site of peak stress was contemporaneously transferred to the connecting rods within an elastic range. In the retrospective clinical study, four patients who had undergone prosthetic reconstruction were included. During a follow-up of 16.6 ± 7.5 months, the walking ability was found preserved in all patients who are still alive and no prosthesis-related complications had occurred except for one hip dislocation. The Musculoskeletal Tumor Society (MSTS) score was found to be 19.5 ± 2.9. Conclusion: The novel reconstructive system yielded favorable biomechanical characteristics and demonstrated promising preliminary outcomes. The method can be used as a reference for reconstruction after type I + II + III hemipelvectomy.